An FPGA Chaos-Based PWM Technique Combined with Simple Passive Filter for Effective EMI Spectral Peak Reduction in DC-DC Converter. (24th February 2014) - Natarajan, Sudhakar; Natarajan, Rajasekar
Abstract : A new and simple but effective electromagnetic interference suppression technique based on field programmable logic array (FPGA) technology to provide a significant EMI noise attenuation in DC-DC converters is discussed. The voltage controlled boost converter for EMI reduction is analyzed using FFT under traditional PWM technique and chaotic mode operation. This technique aids the DC-DC converters to comply in specified EMI limits and replace conventional bulky passive filter with a simple passive filter. A prototype model has been tested and hardware results show significant reduction of EMI in chaotic mode operation of the boost converter.